Implementasi Metode ICONIX Proces Pada Aplikasi Pemesanan Jasa Make Up Artist Berbasis Android - Suhartini, Suhartini; Fajriyah, Fajriyah; Purbasari, Yuntari; Maryani, Maryani (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2025)
Sanggar Bibib is a well-known makeup artist service provider in Prabumulih City. Sanggar Bibib's booking system is still conventional, relying on old methods such as SMS, telephone, WhatsApp, or in-person meetings, because it lacks a systematic ordering system and underutilizes existing technology. Furthermore, potential customers are still embarrassed to ask about the price of makeup services. Based on the results of this research, the author attempted to design an Android-based booking system to facilitate the process of ordering makeup artist services at Sanggar Bibib. This booking system is expected to enable ordering so that negotiations are not lengthy and potential customers don't have to ask directly to find out the price list